Media Roda Iqra dalam Peningkatan Keterampilan Menulis Kalimat Sederhana Bahasa Arab - Sari, Della Puspita; Saleh, Nurming; Bachtiar, Fauziah (Universitas Negeri Makassar, 2025)
Abstract. This study aims to investigate the planning, process, and outcomes of improving sentence writing skills in Arabic language learning using the Iqra Wheel media. This research is a Classroom Action Research (CAR). The subjects of this study are 25 students from grade VIII at MTs Muhammadiyah Ballo. The data collection techniques used are tests of simple sentence writing skills and observation. This study consists of two cycles. This research aims to determine the planning, process and results of improving sentence writing skills in learning Arabic using the iqro wheel media. This type of research is Classroom Action Research (PTK). The subjects of this research were class VIII students at MTs Muhammadiyah Ballo with a total of 25 students. The data collection techniques used were simple sentence writing skills tests and observation. This research consists of two cycles. The results of observation in cycle I, the teacher has not implemented the iqro wheel media according to the steps, so that students cannot write sentences correctly and this still achieves sufficient qualifications with a score of 83. And the results in cycle II, all the steps in the iqro wheel media have all been implemented and students can already write simple sentences, this achieves very good qualifications with a score of 94. And the test results show that the first cycle in qualifications is less with a score of 53, then the second cycle test results show that the use of iqro wheel media can improve the skills of writing simple sentences with qualifications enough with a score of 75. These results show that students' simple writing skills in Arabic have increased with the standard Iqro wheel media in learning ArabicKeywords: : Iqro wheel media, writing skills, Arabic sentences